Sex-specific association of total mineral intake with pulmonary function in middle-aged and older adults with chronic obstructive pulmonary disease - HuanRui Zhang; Wen Tian; GuoXian Qi; XiuFang Wei (Scientific Reports)
Abstract The objective of this study is to assess the impact of dietary intake and supplementation of total magnesium, iron, zinc and selenium on pulmonary function in middle-aged to elderly individuals diagnosed with chronic obstructive pulmonary disease (COPD). This study utilized publicly available data from NHANES, focusing on the 2007–2012 cycles to include participants aged 50 and above with COPD. The definition of COPD followed the 2024 Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines. Dietary mineral intake was assessed through two 24-h dietary recall surveys. Pulmonary function assessments included parameters such as forced expiratory volume in the first second (FEV1), forced vital capacity (FVC), forced mid-expiratory flow (FEF 25–75%), and peak expiratory flow (PEF). Sex-specific associations of total magnesium, iron, zinc, and selenium intakes with pulmonary function parameters were assessed using multivariable regression models adjusted by potential covariates. The study sample had a mean age of 64.56 ± 8.26 years, with 35% being female. The median intakes of total magnesium, iron, zinc, and selenium for males were 312.8 mg, 15.6 mg, 14.4 mg, and 127.9 mcg, respectively, while for females, they were 257.5 mg, 12.8 mg, 11.4 mg, and 96.2 mcg. In males, higher total magnesium and iron intake were significantly associated with increased FEV1, FVC, and PEF (P < 0.05), while in females, only total zinc intake showed a positive association with PEF (P < 0.05). Participants meeting the recommended dietary allowance for total magnesium also exhibited significantly better lung function outcomes in both sexes. This study highlights the importance of adequate dietary mineral intake in managing pulmonary health among COPD patients. Enhancing mineral consumption, particularly magnesium, and iron, may be a viable strategy for improving lung function and overall health in this population, especially in men.